Investigation Into the Relationship Between Sperm Cysteine-Rich Secretory Protein 2 (CRISP2) and Sperm Fertilizing Ability and Fertility of Boars - Gao, Fenglei; Wang, Ping; Wang, Kai; Fan, Yushan; Chen, Yuming; Chen, Yun; Ye, Chao; Feng, Meiying; Li, Li; Zhang, Shouquan; Wei, Hengxi (Frontiers in Veterinary Science, 2021)
The proteins in the seminal plasma and on the sperm surface play important roles in sperm function and numerous reproductive processes. The cysteine-rich secretory proteins (CRISPs) are enriched biasedly in the male reproductive tract of mammals, and CRISP2 is the sole member of CRISPs produced during spermatogenesis; whereas the role of CRISP2 in fertilization and its association with fertility of boars are still unclear. This study aimed to investigate the relationship between the sperm CRISP2 and boar fertility, and explore its impact sperm fertilizing ability. The levels of CRISP2 protein in sperm were quantified by ELISA; correlation analysis was performed to evaluate the association between CRISP2 protein levels and boar reproductive parameters. Meanwhile, the expression of CRISP2 in boar reproductive organs and sperm, and the effects of CRISP2 on in vitro fertilization (IVF) were examined. The results showed that boars with high sperm levels of CRISP2 had high fertility. The protein levels of CRISP2 in sperm were positively correlated with the litter size (r = 0.412, p = 0.026), the number of live-born piglets (r = 0.421, p = 0.023) and the qualified piglets per litter (r = 0.381, p = 0.042). CRISP2 is specifically expressed in the testis and sperm of adult boars, and its location on sperm changed mainly from the post-acrosomal region to the apical segment of acrosome during capacitation. The cleavage rate was significantly decreased by adding the anti-CRISP2 antibody to the IVF medium, which indicates CRISP2 plays a critical role in fertilization. In conclusion, CRISP2 protein is specifically expressed in the adult testis and sperm and is associated with sperm fertilizing ability and boar fertility. Further mechanistic studies are warranted, in order to fully decipher the role of CRISP2 in the boar reproduction.